2021
DOI: 10.1016/j.media.2021.102132
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Linear modeling approach to bootstrapping multi-frame PET image data

Abstract: PET imaging is an important diagnostic tool for management of patients with cancer and other diseases. Medical decisions based on quantitative PET information could potentially benefit from the availability of tools for evaluation of associated uncertainties. Raw PET data can be viewed as a sample from an inhomogeneous Poisson process so there is the possibility to directly apply bootstrapping to raw projection-domain list-mode data. Unfortunately this is computationally impractical, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…2 ). Numeric studies ( 10 , 11 ) have shown that image-domain DGP bootstrapping matches the accuracy of the much more computationally intensive list-mode bootstrapping approach of Haynor and Woods ( 19 ).…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…2 ). Numeric studies ( 10 , 11 ) have shown that image-domain DGP bootstrapping matches the accuracy of the much more computationally intensive list-mode bootstrapping approach of Haynor and Woods ( 19 ).…”
Section: Methodsmentioning
confidence: 89%
“…NPRM approximates the voxel-level residue by the positive linear sum-of-basis elements that have been selected by a cross-validation–guided analysis of a comprehensive collection of time courses produced by segmentation of all the available data in the study ( 10 , 18 ). Individual basis elements are of the form for k of 1, 2,…, K. Here, R k is the basis element residue and Δ k is its associated delay factor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on (17), an image-domain bootstrap data generation process can be defined by the spatial and temporal patterns of model residuals [135,136]. It has been used to assess the uncertainty (standard errors) of parametric imaging [137].…”
Section: Non-parametric Residue Mappingmentioning
confidence: 99%
“…Based on the analysis provided in (Gu et al 2021 ) the optimal statistical combination of separate estimators is the covariance-weighted average of the individual estimators, i.e. where is the covariance of the j th estimator—this might evaluated using a suitable bootstrapping process (O’Sullivan et al 2021 ). The current implementation uses a more simplified weighted averaging process.…”
Section: Theorymentioning
confidence: 99%